microRNA-214-mediated UBC9 expression in glioma - Zhao, Zhiqiang (Korean Society for Biochemistry and Molecular Biology, 2012)
It has been reported that ubiquitin-conjugating enzyme 9 (Ubc9), the unique enzyme2 in the sumoylation pathway, is up-regulated in many cancers. However, the expression and regulation of UBC9 in glioma remains unknown. In this study, we found that Ubc9 was up-regulated in glioma tissues and cell lines compared to a normal control. UBC9 knockdown by small interfering RNA (siRNA) affected cell proliferation and apoptosis in T98G cells. Further experiments revealed that microRNA (miR)-214 directly targeted the 3' untranslated region (UTR) of UBC9 and that there was an inverse relationship between the expression levels of miR-214 and UBC9 protein in glioma tissues and cells. miR-214 overexpression suppressed the endogenous UBC9 protein and affected T98G cell proliferation. These findings suggest that miR-214 reduction facilitates UBC9 expression and is involved in the regulation of glioma cell proliferation. [BMB Reports 2012; 45(11): 641-646]